ALTRUISM AND MORAL ENHANCEMENT (Revista Kriterion, 2021)
In this article I will be discussing what altruism is, distinguishing altruistic motivations (pure and impure) and altruistic behaviour (soft and robust). Pure altruism is when the motivation to benefit another is exclusively to increase the other´s welfare, and impure altruism is when the motivation to benefit another is solely to increase your own wellbeing, or includes on some level, increasing your own welfare. Soft altruism is helping behaviour and robust altruism is improving the welfare of another individual at the expense of the altruist. Having made these distinctions I move on to show that altruism is a requirement of morality. I argue that the three main principles of morality (categorical imperative, golden rule and the greatest happiness principle) are not only compatible with, but also recommend soft altruism. Finally I argue that the probability of people continuing to practise altruistic acts is higher when we are purely motivated, and if that is the case not only classic moral enhancement but also biotechnological moral enhancement can have a role in bringing people over to the altruistic side, stimulating their ‘other regarding’ motivations, thus contributing to spreading altruistic behaviour and morality throughout the world.